A combined treatment with melatonin and andrographis promotes autophagy and anticancer activity in colorectal cancer. (28th January 2022) - Zhao, Yinghui; Wang, Chuanxin; Goel, Ajay
Abstract: Colorectal cancer (CRC) is one of the most frequent malignancies worldwide and remains one of the leading causes of cancer-related deaths in the USA. The high degree of morbidity and mortality associated with this disease is largely due to the inadequate efficacy of current treatments as well the development of chemoresistance. In recent years, several pharmaceutical agents screened from natural products have shown the promise to offer a safe, inexpensive and synergistically multi-targeted treatment option in various cancers. Given the growing evidence of anti-carcinogenic properties of two natural compounds, melatonin (MLT) and andrographis (Andro), we aimed to evaluate their synergistic anticancer effects in CRC. We demonstrate that indeed these two compounds possessed a synergistic anticancer effect in terms of their ability to inhibit cell viability, suppression of colony-formation and induction of apoptosis ( P < 0.05). In line with our in vitro findings, we were able to validate this combinatorial anticancer activity in xenograft animal models ( P < 0.001) as well as tumor-derived 3D organoids ( P < 0.01). RNA-sequencing analysis revealed candidate pathways and genes that mediated antitumor efficacy of MLT and Andro in CRC, among which autophagy pathway and related genes, including NR4A1, CTSL and Atg12, were found to be primarily responsible for the increased anticancer effect by the two natural products. In conclusion, our data reveal a potent and synergistic therapeutic effect of MLT and Andro in the treatment of CRC and provides a rationale for suppressing autophagy in cancer cells as a potential therapeutic strategy for CRC. Abstract : We systematically used multiple in vitro and in vivo models to demonstrate melatonin and andrographis exhibit pronounced synergistic activity in CRC inhibition, mediated in part by autophagy-associated pathways induced apoptotic activation, highlighting the combinatorial therapeutic potential of these two natural products in patients with CRC. Graphical Abstract: